Dissolution and Separation of Wood Biopolymers Using Ionic Liquids - Muhammad, N. (Wiley-Blackwell, 2015)
The majority of the world energy needs have been supplied from petroleum resources. While they are an efficient energy provider, their usage has caused pollution problems that warrant the need to search for efficient and cleaner energy sources. The ever growing global demand of energy and the concerns for the environment have prompted researchers to develop convenient and efficient ways to convert biomass into valuable chemicals, bio-fuels, and useful biomaterials. This review focuses on the application of ionic liquids for the dissolution of wood biomass and wood-derived compounds. The factors which affect the dissolution of cellulose and lignin in ionic liquids are described as well as the effects of ionic liquids on the physical properties of cellulose. The use of ionic liquids alone or in combination with other co-solvent systems which help in the fractionation of wood biomass are discussed. Additionally, the cost economic aspects of ionic liquid applications are highlighted. Copyright Â© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim